Dysbiotic human oral microbiota alters systemic metabolism via modulation of gut microbiota in germ-free mice. Issue 1 (31st December 2022) - Yamazaki, Kyoko; Miyauchi, Eiji; Kato, Tamotsu; Sato, Keisuke; Suda, Wataru; Tsuzuno, Takahiro; Yamada-Hara, Miki; Sasaki, Nobuo; Ohno, Hiroshi; Yamazaki, Kazuhisa
ABSTRACT: Background: The effect of oral microbiota on the intestinal microbiota has garnered growing attention as a mechanism linking periodontal diseases to systemic diseases. However, the salivary microbiota is diverse and comprises numerous bacteria with a largely similar composition in healthy individuals and periodontitis patients. Aim: We explored how health-associated and periodontitis-associated salivary microbiota differently colonized the intestine and their subsequent systemic effects. Methods: The salivary microbiota was collected from a healthy individual and a periodontitis patient and gavaged into C57BL/6NJcl[GF] mice. Gut microbial communities, hepatic gene expression profiles, and serum metabolites were analyzed. Results: The gut microbial composition was significantly different between periodontitis-associated microbiota-administered (PAO) and health-associated oral microbiota-administered (HAO) mice. The hepatic gene expression profile demonstrated a distinct pattern between the two groups, with higher expression of lipid and glucose metabolism-related genes. Disease-associated metabolites such as 2-hydroxyisobutyric acid and hydroxybenzoic acid were elevated in PAO mice. These metabolites were significantly correlated with characteristic gut microbial taxa in PAO mice. Conversely, health-associated oral microbiota were associated with higher levels of beneficial serum metabolites in HAO mice. Conclusion: The multi-omics approach used in this study revealed that periodontitis-associated oral microbiota is associated with the induction of disease phenotype when they colonized the gut of germ-free mice.